The in vitro tracing of miR-144/451 reveals the potential regulatory function of LINC01569 in erythropoiesis - Bingyi LIAO; Wencui SUN; Shili TANG; Enxia HUANG; Qingrong LIU; Yuan XUE; Yonggang ZHANG (Zhongguo shuxue zazhi, 2024)
Objective Utilizing a specially engineered miR-144-GFP-H1 human embryonic stem cell (hESC) reporter line, this study leverages GFP fluorescence as an indicator of miR-144 expression to gauge the progression of erythropoiesis. The investigation is aimed at elucidating the potential roles of lncRNAs within the erythropoietic framework and conducting an initial assessment of their functional impact. Methods The miR-144/451-GFP-H1 cell line (hereafter referred to as 144-H1) was utilized for in vitro erythrocyte induction culture. The subpopulations of cells entering the erythropoiesis stage were characterized by the surface molecules CD71 and GPA. The GFP reporter gene of miR-144 served as a critical determinant to distinguish between GFP-positive cells (with a high propensity for erythropoiesis) and GFP-negative cells (with a low propensity for erythropoiesis). Transcriptome sequencing was performed on both groups to identify differentially expressed long non-coding RNAs (lncRNAs). LncRNA entries with potential for validation were selected for preliminary functional verification. The CRISPR/Cas9 gene editing technique was employed to design functional interference strategies for the targeted lncRNAs, obtaining 144-H1 cell lines with knocked-out function of the specific lncRNAs. These knockout cell lines, along with non-knockout 144-H1 cell lines, were used for parallel erythrocyte induction culture to identify differential nodes. This approach preliminarily verified their impact on erythropoiesis in an in vitro development model. Results 1)The constructed 144-H1 cell line was capable of expressing GFP fluorescence upon entering the stage of in vitro erythrocyte induction, indicating the activation of miR-144/451. 2)Within the CD71, GPA double-positive group, significant differences in lncRNA expression were observed between the GFP-positive and GFP-negative subpopulations. 3) Gene editing strategies involving the deletion of sequence segments capable of effectively interfering with the function of multiple lncRNA entries were designed and verified for successful editing. In the knockout cell lines, parts of the lncRNA sequences were directly deleted. 4)In parallel validation experiments of erythrocyte induction culture, cell lines with LINC01569 knocked out exhibited significant differences in flow cytometric subpopulations and cell proliferation capabilities compared to the non-knockout cell lines: ①The knockout cell lines showed sustained high expression of GFP fluorescence. ②The proportion of the CD71-GPA double-positive group in the knockout cell lines continuously decreased during erythrocyte maturation. ③No significant expression of hemoglobin was observed in the knockout cell lines, lacking the characteristic red color. ④The cell proliferation capability of the knockout cell lines was significantly lower than that of the non-knockout cell lines (P<0.05). Conclusion The successful employment of the 144-H1 cell line facilitated an exploration into the potential functions of lncRNAs in erythropoiesis. This enables the design of more refined in vitro developmental experiments to enhance the precision in capturing lncRNA functions. Among the differentially expressed lncRNA entries, LINC01569 was preliminarily validated to play a regulatory role in erythropoiesis. The functional absence of LINC01569 severely impacts the normal differentiation and proliferation of erythrocytes. The specific regulatory mechanism of LINC01569 in erythropoiesis warrants further investigation and research.